Studi Literatur: Pengaruh Good Corporate Governance Terhadap Underpricing Pada Penawaran Saham Perdana - Aprillia Nabilla Ayu Rosadi; Fadia Ayu Silfia; Mohamad Djasuli (CV. ITTC INDONESIA, 2022)
This literature review aims to discuss the impact of effective corporate governance on underpricing issues for companies conducting an initial public offering (IPO) on the Indonesia Stock Exchange. Based on good corporate governance practices in Asia, Indonesia is a low-ranking company, so this study uses 10 variables approved by the Indonesian Ministry of Research and Technology. Good corporate governance variables include committees, independent committees, board of directors, directors, board of directors and independent directors. The test used as a method is a systematic literature search. The results of this study show empirical evidence that the effectiveness of corporate governance has a positive and negative effect on underpricing.